2004
DOI: 10.1016/j.jasms.2004.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Half protons or doubly charged protons? The history of metastable ions

Abstract: The history of metastable ions is intertwined with that of ions formed by collision-induced dissociation (CID), and frequently the genesis of the two ion types cannot be strictly separated. Originally, metastable ions were considered a curiosity or even a nuisance, being responsible for "humps" in the base line of the recorded mass spectra. In their heyday metastable ions were recognized as having importance for establishing fragmentation sequences and for distinguishing between isomeric ion structures. Today,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Although these metastable peaks provided confirmation of a particular fragmentation path (m 1 + → m 2 + ), they were often considered more of a nuisance than an asset, and indeed some sector instruments included “metastable suppressors” to remove them from the mass spectrum (possible since they had less than full kinetic energy) [3] . But these metastable peaks also offered insight into the fundamentals of ion fragmentation and spawned the development of ion kinetic energy spectroscopy (IKES) and mass-analyzed ion kinetic energy spectroscopy (MIKES) to explore those insights [4] .…”
Section: The Seven Ages Of Analytical Ms/msmentioning
confidence: 99%
“…Although these metastable peaks provided confirmation of a particular fragmentation path (m 1 + → m 2 + ), they were often considered more of a nuisance than an asset, and indeed some sector instruments included “metastable suppressors” to remove them from the mass spectrum (possible since they had less than full kinetic energy) [3] . But these metastable peaks also offered insight into the fundamentals of ion fragmentation and spawned the development of ion kinetic energy spectroscopy (IKES) and mass-analyzed ion kinetic energy spectroscopy (MIKES) to explore those insights [4] .…”
Section: The Seven Ages Of Analytical Ms/msmentioning
confidence: 99%
“…Although MALDI was initially considered to be a soft ionization technique, it was later found that metastable decay (i.e., fragmentation of sample ions) does occur. [19][20][21][22][23][24][25][26][27][28][29] As discussed in detail by Karas,29 there are thought to be primarily three effects which contribute to fragmentation:…”
Section: A Molecular Fragmentation In Maldimentioning
confidence: 99%